Educação, verdade e valor: diálogo com Nietzsche - Oliveira, Thabata Franco de; Valdemarin, Vera Teresa [UNESP] (My University, 2013)
This article shows some reflections on the dilemmas of contemporary education, especially those that go without a horizon of truth and value, that are foundation and justification for the setting up of the modern school. Such reflections are grounded in the texts of Friedrich Nietzsche to discuss the dissolution of metaphysics, regarded here as an element of destabilization of the symbolic repertoire of the school. It is suggested at the end, the recovery of the interpretive act as an alternative to the emptying of the concepts of truth and value and recognition of dialogue as a privileged place to get closer to temporary and circumstantial truth.

Este artigo sistematiza reflexões sobre alguns dilemas da educação contemporânea, principalmente aqueles que prescindem de um horizonte de verdade e de valor, base fundamental e justificativa para a instauração da escola moderna. Tais reflexões estão ancoradas em textos de Friedrich Nietzsche que discutem a dissolução da metafísica, aqui considerada como um dos elementos de desestabilização do repertório simbólico da instituição escolar. Propõe-se, ao final, a recuperação do ato interpretativo como alternativa ao esvaziamento dos conceitos de verdade e de valor e o reconhecimento do diálogo como lugar privilegiado para a aproximação com a verdade provisória e circunstancial.
Keywords: Truth and value; Nietzsche; Contemporary education; Philosophy of education; Verdade e valor; Nietzsche; Educação contemporânea; Filosofia da educação